Thermogravimetric Kinetics and High Fidelity Analysis of Crude Glycerol. (December 2017) - Almazrouei, Manar; Samad, Tala El; Janajreh, Isam
Abstract: This work undertakes the determination of the glycerol thermochemical conversion kinetics in one hand, and the utilize of these quantities in high fidelity reactive flow model on the other. The kinetic parameters of glycerol are determined by using thermogravimetric analyzer (TGA) in the temperature range of 50-700 ͦC. Due to the distinct behavior of the crude glycerol, the TG curves of the thermal decomposition process were divided into several events, moisture release and two-subsequent devolatalization and gasification phases. The kinetic parameters, are calculated using four different methods: Arrhenius, Coats-Redfern, Ingraham Marrier and Differential Method. Results of the kinetics study were nearly consistent within the individual kinetic model but the discrepancy was more obvious amongst the different models. The resulted Coat-Redfirm kinetics were the best fit amongst other four considered methods demonstrated by its highest correlation R 2 . It resulted with activation energy of 62 kJ/mol and 138 kJ/mol and pre-exponential factor of 4.3e5 min -1 and 2.25e9 min -1 for phase 2 and phase 3, respectively. A high fidelity CFD model is developed to assess the performance of glycerol gasification in a tubular reactor. The model is governed by the Navier-stokes equations coupled to species transport equation for reactive flow under non-isothermal conditions. Results of the syngas conversion are in agreement with relevant literature and theoretical molar yield of 0.56 and 0.42 mole fractions for H2 and CO, respectively. The developed reactive flow model has brought more insight into the glycerol gasification, enabling further parametric studies in the pursuit of the optimal reactor design configuration and operating conditions for potential process integration.